Old Code Subject Files
The primary source of this series were Soviet (after 1991, Russian) central newspapers and other periodicals. The series also includes clippings from the Western press, news agency releases, TV and radio monitoring materials, Radio Liberty broadcast transcripts. The Old Code Subject Files (with its 600 subject headings which double in number with sub-headings) covers a wide range of topics reflecting a broad spectrum of life in the Soviet Union. Many of the subject headings are placed under general categories (like Foreign Policy or Population), others are specific to the Soviet reality and only understood it its historical context (like Î÷ęîâňđčđŕňĺëüńňâî which signifies humbug, or fraud committeed against the state; Ëîçóíăč / Slogans which are lists of politically correct texts approved by the Party Central committee to be used in the course of official celebrations of state holidays). In the Old Code Subject Files, few categories are divided into subcategories. As a result, categories of different importance are built into one alphabetical chain in which, for example, Coffee and CP (Communist Party) are set next to each other. In practice, the best method for accessing materials is to scan the whole list of relevant topics. Of particular interest are records reflecting crucial events in the Soviet history, such as the 1968 invasion of Czechoslovakia, the Afghanistan war, the human rights movement, public debates of the Perestroika period, and various aspects of the Soviet foreign policy. Accruals not expected